Complications arising from cardiac implantable electrophysiological devices: review of epidemiology, pathogenesis and prevention for the clinician. Issue 2 (17th February 2016) - Atreya, Auras R.; Cook, James R.; Lindenauer, Peter K.
ABSTRACT: Cardiac implantable electronic devices (CIEDs) which include devices such as permanent pacemakers, implantable cardioverter-defibrillators and cardiac resynchronization therapy devices are well established therapies that have been shown to improve quality of life and prolong survival in appropriately selected patients, and are being increasing utilized across the world. However, CIED implantations are invasive procedures and a thorough understanding of the potential complications is required to prevent deleterious patient outcomes. In this review, we will discuss frequent complications (infection, hematoma or bleeding, and procedural mechanical complications) that may harm patients after CIED implantation, and the steps that can be taken to minimize their risk. This is particularly relevant to trainees/ clinicians who either perform these procedures or refer patients for CIED implantation.